2022
DOI: 10.1039/d2cc04911b
|View full text |Cite
|
Sign up to set email alerts
|

Charge transport in liquid crystal network of terthiophene-siloxane block molecules

Abstract: We report that mesogens consisting of a terthiophene core and discrete oligodimethylsiloxane side-chains terminated by acrylate units can be photopolymerized in the columnar phase with retention of nanoscale order and charge transport capabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…[11][12][13][14] An effective strategy to create versatile nanostructured organic materials is based on sidechain engineering. [15][16][17] In the past, discrete oligodimethylsiloxane (oDMS, Ð < 1.00001) have been introduced in end-functionalized molecules, which self-assemble into 2D materials. [18,19] These phase-separated structures are exploited to translate molecular events to a macromolecular level, exemplified by diphenylanthracene-based molecules that exhibit a hundredfold increase in photon-upconversion in an ordered material compared to its disordered counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] An effective strategy to create versatile nanostructured organic materials is based on sidechain engineering. [15][16][17] In the past, discrete oligodimethylsiloxane (oDMS, Ð < 1.00001) have been introduced in end-functionalized molecules, which self-assemble into 2D materials. [18,19] These phase-separated structures are exploited to translate molecular events to a macromolecular level, exemplified by diphenylanthracene-based molecules that exhibit a hundredfold increase in photon-upconversion in an ordered material compared to its disordered counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…18,20 Recently, our group and others have shown that discrete oDMS (Ð o 1.00001) can greatly enhance the phase separation and nanoscale ordering of materials. [21][22][23][24] Yet, to the best of our knowledge, D-A polymers with longer and/or branched oDMS side chains have not been reported. In previous years, we have reported on the synthesis of elongated and branched oDMS as side chains for supramolecular polymers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the anisotropic LC nanostructures can endow the materials with excellent mechanical properties. Nanostructured materials through polymerization of reactive liquid crystals have enormous potential in various applications [16][17][18] involving electron transport, [19][20][21] ion transport, [22][23][24][25][26][27] electrochromism, 28 thermal conductivity, 29 molecular absorption and separation, [30][31][32][33][34][35] catalysts, 36 and actuator and shape-memory materials. [37][38][39][40][41][42] Our intention is to develop a low-voltage driven iEAP actuator that exhibits large strain and high force by designing photopolymerized LC membranes with channels of ionic liquids.…”
Section: Introductionmentioning
confidence: 99%